Firm-Value Effects of Carbon Emissions and Carbon Disclosures - Matsumura, Ella Mae; Prakash, Rachna; Vera-Muñoz, Sandra C. (The Accounting Review, 2014)
ABSTRACT Using hand-collected carbon emissions data for 2006 to 2008 that were voluntarily disclosed to the Carbon Disclosure Project by S&P 500 firms, we examine the effects on firm value of carbon emissions and of the act of voluntarily disclosing carbon emissions. Correcting for self-selection bias from managers' decisions to disclose carbon emissions, we find that, on average, for every additional thousand metric tons of carbon emissions, firm value decreases by $212,000, where the median emissions for the disclosing firms in our sample are 1.07 million metric tons. We also examine the firm-value effects of managers' decisions to disclose carbon emissions. We find that the median value of firms that disclose their carbon emissions is about $2.3 billion higher than that of comparable non-disclosing firms. Our results indicate that the markets penalize all firms for their carbon emissions, but a further penalty is imposed on firms that do not disclose emissions information. The results are consistent with the argument that capital markets impound both carbon emissions and the act of voluntary disclosure of this information in firm valuations. JEL Classifications: G14, Q51, M14. Data Availability: Data are available from the sources identified in the study.